Novel fluorescent cationic benzothiazole dye that responds to G-quadruplex aptamer as a novel K+ sensor. Issue 18 (23rd August 2017) - Sun, Xin; Li, Qian; Xiang, Junfeng; Wang, Lixia; Zhang, Xiufeng; Lan, Ling; Xu, Shujuan; Yang, Fengmin; Tang, Yalin
Abstract : A fluorescent cationic benzothiazole dye that selectively targets a G-quadruplex aptamer was designed and synthesized as a K + sensor. Abstract : A fluorescent cationic benzothiazole dye that selectively targets a G-quadruplex aptamer was designed and synthesized as a K + sensor. The K + -driven aptamer sensor is based on the strategy of conformational transition from single-stranded DNA to G-quadruplex structure, leading to an amplified fluorescence signal in the reporter. This fluorescent sensor displayed high selectivity for K +, suggesting great potential for practical applications.